Ethical Implications of Religious Education: Navigating Values in a Secular World - Elsavira Nurizzah; Edo Indrawan Purwoko; Erna sustiawati (International Forum of Researchers and Lecturers, 2024)
This article explores the ethical implications of teaching religious education in a predominantly secular world. It examines the challenges religious educators face when imparting moral and ethical teachings in societies where secularism and religious pluralism are on the rise. The paper argues for a balanced approach that respects diverse beliefs while fostering ethical responsibility.